The Effects of a Resilience Enhancing Nursing Program on Depression among Pregnant Teenagers - KUASIT, Umaporn; CHUNUAN, Sopen; HATTHAKIT, Urai; BULLOCK, Linda F. C. (Walailak Journal of Science and Technology (WJST), 2020)
The purposes of this study were to evaluate the effects of the resilience enhancing nursing program (RENP) on resilience and depression among pregnant teenagers who received this program. A quasi experimental was conducted with 130 pregnant Thai women. Final analysis included 130 participants (Intervention n = 64 and control group n = 66). The RENP was delivered in three steps including; Step 1, establishing trusting relationships; Step 2, improving the resilience, and Step 3, monitoring and encouraging the resilience practice. The research instruments consisted of a demographic data questionnaire, and resilience and depressive program instruments, including a handbook and self-report. Research data were analyzed and displayed, providing percentage, mean, standard deviation, chi-square, independent t-test, paired t-test, and the repeated measures ANOVA. The findings showed a significant difference in depression by time alone (p = 0.001). However, there was no significant difference by group alone in depression (p = 0.969). This study revealed mean score on depression in the experimental group was not significantly lower than before entering the program at week 4 and week 8 (p = 0.870, p = 0.428). However, resilience showed difference in score over time between the experimental group and control group. There was a significant difference in resilience score by time alone (F = 10.523, p < 0.001). The results can contribute to guiding nurses to enhance decrease in depression in pregnant teenagers in the earlier first trimester in antenatal care units. Nurse or nurse midwife should be concerned about the potential for early detection in the prenatal period and provide appropriate interventions to teenage mothers in the postnatal period.